An economic evaluation of laparoscopy and open surgery in the treatment of tubal pregnancy - Ben W.J Mol; Petra J. Hajenius; Simone Engelsbel; Willem M. Ankum; Fulco Van derVeen; Douwe J. Hemrika; Patrick M.M. Bossuyt (Acta Obstetricia et Gynecologica Scandinavica, 1997)
Background. Laparoscopy has generally replaced open surgery in the treatment of ectopic pregnancy. This study assesses the impact of the introduction of laparoscopy in the surgical treatment of tubal pregnancy on costs. Methods. Consecutive patients undergoing primary surgery for tubal pregnancy between January 1992 and December 1995 were included in the study. Surgery was performed laparo‐scopically or by open surgery. Cost for each treatment was calculated by multiplying resources used with calculated resource unit prices. The analysis was stratified for radical and conservative surgery. Results. Data of 255 patients were analysed. Tubal pregnancy was successfully treated in all patients. Costs per patient were US$ 3,490 for radical open surgery, US$ 1,872 for radical laparoscopic surgery, US$ 3,420 for conservative open surgery and US$ 2,125 for conservative laparoscopic surgery. Differences in costs were caused by a decreased duration of hospital stay after laparoscopy, and, in case of conservative surgery, by an increased persistent tropho‐blast rate after laparoscopy. Conclusions. Laparoscopy is equally effective as open surgery in the treatment of tubal pregnancy, and considerably reduces costs